AHA’s Life’s Essential-8 cardiovascular health metrics and progression of coronary artery calcification in Japanese men - Rajib Mondal; Aya Kadota; Yuichiro Yano; Sayaka Kadowaki; Sayuki Torii; Keiko Kondo; Akiko Harada; Megumi Kawashima; Itsuko Miyazawa; Hiroyoshi Segawa; Takashi Hisamatsu; Yoshiyuki Watanabe; et al. (American Journal of Preventive Cardiology)
Background and aims: The American Heart Association’s Life’s Essential-8 (LE8) cardiovascular health (CVH) metrics is considered a comprehensive framework for optimal cardiovascular wellbeing. However, its relationship with the progression of subclinical atherosclerosis, like coronary artery calcification (CAC), is not clarified. We investigated the associations of LE8 CVH metrics with the prevalence and progression of CAC in Japanese men. Methods: We analyzed data from 760 asymptomatic men participating in the Shiga Epidemiological Study of Subclinical Atherosclerosis. We assessed baseline (2006–2008) LE8 CVH (low, 0–49 points; moderate, 50–79 points; high, 80–100 points) using its eight components (diet, physical activity assessed by step count, smoking, sleep, body mass index, blood lipids, blood glucose, blood pressure). We quantified CAC at baseline and follow-up of 5 years employing Agatston’s method and defined its baseline prevalence (CAC >0) and progression (employing Berry’s criteria). Modified Poisson regression analyses were used to estimate risk ratio (RR) and 95 % confidence interval (CI), adjusted for age and family history of cardiovascular disease. Results: Participants (mean [SD] age, 63.8 [9.4] years) had 63.2 % and 44.9 % prevalence of CAC at baseline and CAC progression at follow-up, respectively. Individuals with moderate and low CVH at baseline had a higher risk of prevalent CAC (RR [95 % CI], 1.42 [1.18–1.71] and 2.07 [1.67–2.57], respectively) at baseline, compared to those with high CVH. Those with moderate and low CVH at baseline had a higher risk of CAC progression (RR [95 % CI], 1.52 [1.17–1.97] and 1.99 [1.42–2.81], respectively), compared to high CVH individuals. Conclusions: A lower LE8 CVH is significantly associated with a higher risk of prevalence and progression of CAC in general Japanese men.